2019
DOI: 10.1097/sla.0000000000003300
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent and Iodized Emulsion for Preoperative Localization of Pulmonary Nodules

Abstract: Objective: This study was conducted to develop a fluorescent iodized emulsion comprising indocyanine green (ICG) solution and lipiodol (ethiodized oil) and evaluate its feasibility for use in a clinical setting. Background: ICG use for the preoperative localization of pulmonary nodules is limited in terms of penetration depth and diffusion. Methods: First, fluorescent microscopy was used to investigate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 29 publications
0
50
0
Order By: Relevance
“…ICG has also been applied to CT-guided preoperative marking of lung nodules with safe and feasible results (20)(21)(22). Recent research has investigated the optimal ICG solution and lipiodol mixture emulsion with safe and successful out comings (23). To the best of our knowledge, little study has been focusing on the comparison between ICG and conventional hook-wire localization.…”
Section: Introductionmentioning
confidence: 99%
“…ICG has also been applied to CT-guided preoperative marking of lung nodules with safe and feasible results (20)(21)(22). Recent research has investigated the optimal ICG solution and lipiodol mixture emulsion with safe and successful out comings (23). To the best of our knowledge, little study has been focusing on the comparison between ICG and conventional hook-wire localization.…”
Section: Introductionmentioning
confidence: 99%
“…The Chinese Experts' Consensus of Preoperative-assisted Localization of Pulmonary Nodules (2019 version) recommends localization methods using liquid materials, including ICG, as a 2A-level technique [15]. Rho J et al [16] found that an optimal emulsion of 10% ICG and 90% lipiodol mixed through 90 passages exhibited an even distribution and the highest signal intensity under uorescence microscopy and that all emulsion types injected were well localized around the target nodules without any side effects or procedure-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…ICG has been widely used in surgery for several organs (i.e., hepatic segmentectomies). In the thoracic field, ICG was used for identifying sentinel lymph nodes or tumor localization initially (3)(4)(5). With regard to conditions in the esophagus, ICG is used to prevent the complication of chylothorax during esophagectomy, which is performed to identify the thoracic duct (9).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, indocyanine green (ICG) fluorescence has been used to solve the following two problems in thoracic surgery: first, identification of the accurate intersegmental plane in anatomical lung segmentectomy for detecting areas of residual pulmonary blood flow (3)(4)(5) and, second, displaying the location of the tumor or optimal resection line intraoperatively as ICG virtual-assisted lung mapping (ICG-VAL-MAP) (6). Herein, we introduce images and videos that describe the features of surgery using the new ICG technology in the field of minimally invasive thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%